Proceedings of SPE EUROPEC/EAGE Annual Conference and Exhibition 2010
DOI: 10.2523/131103-ms
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Flooding - Flow Properties in Porous Media versus Rheological Parameters

Abstract: Mobility reduction is one of the critical parameters in polymer flooding. The EOR polymers have shear thinning bulk rheology, while core flood experiments with hydrolysed polyacrylamide (HPAM) in this paper show four different viscosity regimes. Through a systematic work, in which the molecular weight and degree of hydrolysis as well as the permeability and brine salinity were varied, the apparent viscosity was well-matched with theoretical models. The following four viscosity regimes were identified: (i) At l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…Typically, elastic effects become dominant in artificial porous media when the Deborah numbers are in the range of 0.1 and 10. [71,[77][78][79] Vossoughi and Seyer [80] reported that the elastic influence on the flow resistance occurs at the critical Deborah number of 0.08 in artificial porous media. Skartsis el al.…”
Section: Extensional Viscosity Versus Strain Ratementioning
confidence: 99%
“…Typically, elastic effects become dominant in artificial porous media when the Deborah numbers are in the range of 0.1 and 10. [71,[77][78][79] Vossoughi and Seyer [80] reported that the elastic influence on the flow resistance occurs at the critical Deborah number of 0.08 in artificial porous media. Skartsis el al.…”
Section: Extensional Viscosity Versus Strain Ratementioning
confidence: 99%
“…Likewise, Stavland et al (2010) and Norris (2011) presented a comparable but simpler rheological model that also covered the shear thinning and shear thickening viscosity regions. Unexpectedly, this model showed that the apparent viscosity decreased beyond the shear thickening regime with increasing shear rate during coreflooding tests.…”
Section: Shear Thickening Effectmentioning
confidence: 99%
“…The velocity enhancement that polymer shows in porous media was incorporated using a velocity enhancement factor defined by (Sorbie, 1991) and (Stavland, 2010) as,…”
Section: Polymer Velocity Enhancementmentioning
confidence: 99%